Students' Deductive Reasoning in Evaluating Solutions to Geometry Problems - Rahmah, Aulia; Dewi, Silvia Kumala; Kohar, Ahmad Wachidul (Universitas Negeri Surabaya, 2023)
Deductive reasoning is very important in learning mathematics and is one of the formal goals that emphasizes the arrangement of reasoning. This is a qualitative research that aims to describe the deductive reasoning abilities of junior high school students in evaluating problem solutions in geometry material. The subjects of this study were two junior high school students in Gresik who had high mathematical abilities and were of different genders. The instrument used was task-based interviews. The task in question is a deductive reasoning ability test in which there are problems and their solutions. Data analysis was carried out using three indicators of deductive reasoning according to Sumarmo: carrying out calculations based on certain formulas, conducting proofs, and drawing conclusions. The results showed that the deductive reasoning abilities of female and male students were relatively the same. In solving the problem, Both male and female students had similar initial idea by making an example of the length of the side of the given object. However, male students are more capable of proving and considering more effective strategies for solving problems. Therefore, students and teachers need to improve their deductive reasoning abilities and consider all effective strategies for solving problems.